THE DEGREE OF EXPRESSIVENESS CONVEYED THROUGH INTERROGATIVE SENTENCES IN A WORK OF PUBLICIST FICTION (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
This article examines the level of expressiveness conveyed by interrogative sentences in a piece of publicist fiction. By qualitatively analyzing the structure of interrogatives, the study seeks to determine how effectively they evoke emotional reactions and captivate readers in publicist fiction. The outcomes of this investigation contribute to our comprehension of how interrogative sentences enhance expressive communication in literary settings.